Majaz Isti'arah (Metaphor) Review of the Word Qiradatan (Ape) in Contemporary Tafsir (Case Study of Ashabus Sabat in Tafsir Quraish Shihab and Tafsir Wahbah Zuhaili) - Luthfi Zainul Muktashi; Andri Nirwana AN; Sufian Suri; Fuadi (al-Afkar, Journal For Islamic Studies, 2024)
The aim of this research is to find out the meaning of the word qiradatan (ape) which is found in several verses in the Qur'an, whether this word contains the full meaning of ape or just its nature. Researchers examine the meaning of the word qiradatan using contemporary interpretations, namely the Quraish Shihab interpretation and the Wahbah Zuhaili interpretation. The method used in this research is a qualitative method which leads to an explanation of the descriptive analysis model, namely classifying the word "qirodatan" by describing it, then analyzing its implications. The approach applied in this research is a language and language approach, with data collection techniques through library research. The research carried out resulted in the conclusion that the word monkey has a deeper meaning than just an animal. The word monkey here shows the nature of this animal. The curse of being a monkey is because monkeys are animals that always reveal their private parts. The contrasting shape of their fur and skin means that the private parts of monkeys are very visible so that the monkeys here have no shame.